2022
DOI: 10.1111/dme.14891
|View full text |Cite
|
Sign up to set email alerts
|

Management of type 1 diabetes in low‐ and middle‐income countries: Comparative health system assessments in Kyrgyzstan, Mali, Peru and Tanzania

Abstract: Aims: To describe and compare the health system responses for type 1 diabetes in Kyrgyzstan, Mali, Peru and Tanzania. Methods:The Rapid Assessment Protocol for Insulin Access, a multi-level assessment of the health system, was implemented in Kyrgyzstan, Mali, Peru and Tanzania using document reviews, site visits and interviews to assess the delivery of care and access to insulin.Results: Despite the existence of noncommunicable or diabetes strategies and Universal Health Coverage policies including diabetes-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…Differences across countries and informant groups are likely driven by varying socioeconomic status, clinical needs, health system access and levels of diabetes knowledge. 3 Indeed, knowledge of some of the currently available NI-MI-GMDs differed across countries, with informants from Kyrgyzstan and Peru providing more detailed user requirement narratives due to greater knowledge of devices accessible in their contexts than their counterparts in Mali and Tanzania. This difference highlights the challenge of designing NI-MI-GMDs for use in LMICs, which vary according to current level of NI-MI-GMD use as well as readiness to adopt or expand NI-MI-GMD use due to differences in infrastructure, technology and expertise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences across countries and informant groups are likely driven by varying socioeconomic status, clinical needs, health system access and levels of diabetes knowledge. 3 Indeed, knowledge of some of the currently available NI-MI-GMDs differed across countries, with informants from Kyrgyzstan and Peru providing more detailed user requirement narratives due to greater knowledge of devices accessible in their contexts than their counterparts in Mali and Tanzania. This difference highlights the challenge of designing NI-MI-GMDs for use in LMICs, which vary according to current level of NI-MI-GMD use as well as readiness to adopt or expand NI-MI-GMD use due to differences in infrastructure, technology and expertise.…”
Section: Discussionmentioning
confidence: 99%
“…7 For all PLWD needing tools to monitor their blood glucose, the lack of access to affordable equipment in LMICs gives rise to low levels of monitoring, contributing to poor glycaemic control and, as a result, poor disease outcomes. 3 7–9 …”
Section: Introductionmentioning
confidence: 99%
“…The cost, price, and availability of glucometer strips emerged as significant factors influencing self-monitoring practices, consistent with prior research that highlighted the financial burden and cost limitations associated with blood glucose monitoring ( 10 , 23 - 26 ). The cost of glucometer strips and the price of glucometers in low to middle-income countries can amount to a significant portion of the lowest-paid government workers’ wages, ranging from 4 to 29.9 days, depending on the coverage of T1DM care by the government ( 27 ). This underscores the crucial role of price and availability of glucometers and strips in achieving the standard of care for T1DM patients, as highlighted by the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
“…1 Current quality of care for type 1 diabetes, as expressed by access to medicines and supplies or specialized care, has been reported to be inadequate in different countries, especially in low-and middle-income countries. 2 Some reasons are the challenges in accessing healthcare and that existing health systems interventions are not necessarily adapted for the complex management of type 1 diabetes. A previous review on health system interventions found that studies mainly focused on delivery of care and failed to assess other types of interventions such as financial arrangements, legal or policy interventions or implementation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, approximately 9 million people live with type 1 diabetes 1 . Current quality of care for type 1 diabetes, as expressed by access to medicines and supplies or specialized care, has been reported to be inadequate in different countries, especially in low‐ and middle‐income countries 2 . Some reasons are the challenges in accessing healthcare and that existing health systems interventions are not necessarily adapted for the complex management of type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%